Weeds and agro by-products for sustainable farming of edible field cricket, Gryllus madagascarensis (Orthoptera: Gryllidae) - Henlay J. O. Magara; Cédrique L. Solofondranohatra; Sylvain Hugel; Brian L. Fisher (PLoS ONE, 2025)
Gryllus madagascarensis (Orthoptera: Gryllidae) is a cricket species that shows promise to mitigate food insecurity and malnutrition. But whether this species will accept low- to no-cost weeds and agro by-products as feed, and how these feeds affect its performance, remains unknown. This study assessed the acceptability of 66 weed species and agro by-products (derived from a single plant species) by adult G. madagascarensis and compared the results to a reference feed (chicken feed). We further examined how the 11 top acceptable single plant products affected growth parameters of G. madagascarensis. The parameters assessed included development, survivorship, body mass and body length and reproductive fitness of the crickets on each of these diets. Finally, the costs of the 11 top accepted single plant products were compared. Our results demonstrated that the cricket accepted all 66 single plant products at varying degrees. Tropical white morning glory (Ipomoea alba), cassava tops (Manhot esculentum), taro leaves (Colocasia esculenta), cowpea bran (Vigna unguiculata), American hog-peanut (Afroamphica africana), gallant soldier (Galinsoga parviflora), wheat bran (Triticum aestivum), glycine (Neonotonia wightii), silver leaf Desmodium (Desmodium uncinatum), maize bran (Zea mays) and rice bran (Oryza sativa) were the most accepted. The analysed nutrient content varied across the top 11 accepted single plant products and the reference feed. The shortest development and highest survival rate were recorded with gallant soldier and cowpea bran powders. Wet body mass and body length were highly impacted by various single plant products tested compared to the reference feed. Reproductive parameters were significantly briefer on tropical white morning glory compared to other feeds and the reference diet. Single plant products cost two- to four-fold less than reference feed. The findings are valuable for developing blended diets that balance performance, cost and availability for household and commercial production of crickets as a “green” technology for producing edible sources of protein.